Collaboration and Technology Transfer in the Defense Industry as Drivers of Innovation and Global Security Enhancement - Ariputro, Aryobimo Bharadian; Syahtaria, Mohamad Ikhwan; Trismadi, Trismadi; Suwarno, Panji; Widodo, Pujo; Purwanto, Dwi Ari (Physical Sciences, Life Science and Engineering, 2024)
Collaboration and technology transfer in the defense industry play a crucial role in enhancing military capabilities, reducing dependence on imports, and strengthening national and global security. Through international cooperation, countries can share advanced technology, technical expertise, and development costs, which not only increase efficiency but also drive innovation in the defense sector. This collaboration also brings significant economic benefits, including job creation, local industry development, and increased investment in research and development (R&D). However, challenges such as differing national interests, technical coordination, and intellectual property protection need to be addressed to ensure the success of collaborative projects. This study employs a qualitative descriptive methodology to explore and describe the processes and impacts of collaboration and technology transfer in the defense sector. The results show that international collaboration can facilitate innovation and enhance international security dynamics. To increase the effectiveness of collaboration and technology transfer, improvements in transparency, process standardization, government incentives, local workforce skill development, infrastructure enhancement, and intellectual property protection are needed. By addressing these challenges, international collaboration and technology transfer in the defense industry can more effectively strengthen military and economic capabilities, contributing to better national and global security.